Strategy for the lowering and the assessment of exposure to nanoparticles at workspace - Case of study concerning the potential emission of nanoparticles of Lead in an epitaxy laboratory. (May 2015) - Artous, Sébastien; Zimmermann, Eric; Douissard, Paul-Antoine; Locatelli, Dominique; Motellier, Sylvie; Derrough, Samir
Abstract: The implementation in many products of manufactured nanoparticles is growing fast and raises new questions. For this purpose, the CEA - NanoSafety Platform is developing various research topics for health and safety, environment and nanoparticles exposure in professional activities. The containment optimisation for the exposition lowering, then the exposure assessment to nanoparticles is a strategy for safety improvement at workplace and workspace. The lowering step consists in an optimisation of dynamic and static containment at workplace and/or workspace. Generally, the exposure risk due to the presence of nanoparticles substances does not allow modifying the parameters of containment at workplace and/or workspace. Therefore, gaseous or nanoparticulate tracers are used to evaluate performances of containment. Using a tracer allows to modify safely the parameters of the dynamic containment (ventilation, flow, speed) and to study several configurations of static containment. Moreover, a tracer allows simulating accidental or incidental situation. As a result, a safety procedure can be written more easily in order to manage this type of situation. The step of measurement and characterization of aerosols can therefore be used to assess the exposition at workplace and workspace. The case of study, aim of this paper, concerns the potential emission of Lead nanoparticles at the exhaust of a furnace in an epitaxy laboratory. The use of Helium tracer to evaluate the performance of containment is firstly studied. Secondly, the exposure assessment is characterised in accordance with the French guide "recommendations for characterizing potential emissions and exposure to aerosols released from nanomaterials in workplace operations". Thirdly the aerosols are sampled, on several places, using collection membranes to try to detect traces of Lead in air.